Impact of home care counseling on the quality of life of people with diabetes militus - A Syamsinar Asmi; M. Khalid Fredy Saputra (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Diabetes mellitus is a chronic disease that requires long-term management to control blood sugar levels and prevent complications. The quality of life of diabetics is often affected by this disease, both physically, psychologically, and socially. Home care counseling has been one of the interventions considered effective in assisting diabetics in managing their condition. This study aims to evaluate the impact of home care counseling on the quality of life of people with diabetes mellitus. Methods: This research is quasi-experimental with a randomized pretest and posttest control group design. Samples are taken from patients' medical records and selected by simple random sampling. Results: The mean score before the intervention was 60.55 with a standard deviation of 2.605, which increased to 71.35 with a standard deviation of 4.107 after the intervention. Statistically, there is a difference in the quality of life before and after counseling with a value of p = 0.000 (p < 0.05), which means that home care counseling is effective for sufferers to improve the quality of life of D.M. sufferers. Conclusions: Home care counseling significantly impacts the quality of life of people with diabetes mellitus. These interventions can improve the sufferer's self-management and provide the support needed to overcome the challenges faced in daily life. Therefore, home care counseling is recommended as part of comprehensive management for people with diabetes mellitus.